The Interrelationship between Emotional Intelligence and Linguistic Awareness among Students at the University Level: Cognitive and Social Perspectives - Ahmed, Ban Shihab; Salem, Khalid Nayef (Journal of Tikrit University for Humanities, 2025)
This study aims to investigate the interrelationship between emotional intelligence and linguistic awareness among EFL students, adopting both cognitive and social perspectives. Emotional intelligence encompasses the ability to identify, understand, manage, and use emotions effectively, while linguistic awareness involves the conscious knowledge of language structure and the ability to reflect on language use. This study examines whether students with higher levels of emotional intelligence exhibit greater linguistic awareness and how cognitive and social factors mediate this relationship. This study attempts to answer the question ‘is there any relationship between students’ emotional intelligence and linguistic awareness?’. The sample of present study is college students who study English at Garmian and Tikrit Universities college of Education for human sciences at the Department of English. The research adopts a correlational design, utilizing standardized assessments to measure both emotional intelligence and language awareness among the sample of the study. Findings from this study offer insights into how emotional and cognitive skills interact in language learning contexts, potentially informing teaching practices. Ultimately, this research contributes to the growing body of literature advocating for a holistic view of language education, where emotional intelligence is recognized as an integral component of linguistic and academic competence.